Integrated Analysis of circRNA-miRNA-mRNA ceRNA Network in Cardiac Hypertrophy - Chen, Yang-Hao; Zhong, Ling-Feng; Hong, Xia; Zhu, Qian-Li; Wang, Song-Jie; Han, Ji-Bo; Huang, Wei-Jian; Ye, Bo-Zhi (Frontiers in Genetics, 2022)
Cardiac hypertrophy is an adaptive cardiac response that accommodates the variable hemodynamic demands of the human body during extended periods of preload or afterload increase. In recent years, an increasing number of studies have pointed to a potential connection between <ext-link ext-link-type="uri" xlink:href="http://www.baidu.com/link?url=73FaB3wU5f0dJ01ZwnLM6LlkuVW_GoWxBpU3bf6cVoFP6KYfwDsL40QCtW32u3ilbPte5J8Wlv1B9befJPX7Fa3ieSbaQxY9IIDBGzKW7hvamZEnl-1Q7YK0Ob5Sf2Ue" xmlns:xlink="http://www.w3.org/1999/xlink">myocardial hypertrophy and abnormal expression of non-coding RNAs. Circular RNA (circRNA), as one of the non-coding RNAs, plays an essential role in cardiac hypertrophy. However, few studies have systematically analyzed circRNA-related competing endogenous RNA (ceRNA) regulatory networks associated with cardiac hypertrophy. Therefore, we used public databases from online prediction websites to predict and screen differentially expressed mRNAs and miRNAs and ultimately obtained circRNAs related to cardiac hypertrophy. Based on this result, we went on to establish a circRNAs-related ceRNA regulatory network. This study is the first to establish a circRNA-mediated ceRNA regulatory network associated with myocardial hypertrophy. To verify the results of our analysis, we used PCR to verify the differentially expressed mRNAs and miRNAs in animal myocardial hypertrophy model samples. Our findings suggest that three mRNAs (Col12a1, Thbs1, and Tgfbr3), four miRNAs (miR-20a-5p, miR-27b-3p, miR-342-3p, and miR-378a-3p), and four related circRNAs (circ_0002702, circ_0110609, circ_0013751, and circ_0047959) may play a key role in cardiac hypertrophy.